Thai Foreign Policy in the Form of Public Diplomacy Associated With the Halal Industry - Sudrajat, Arip Rahman (KnE Social Sciences, 2022)
This study aimed to examine the halal industry in relation to Thai public diplomacy. The Thai Government aims to build an image as a country that is friendly to Muslim tourists. This study applied the concept of halal and public diplomacy in understanding Thailand’s economic development policies, especially in the manufacturing and tourism sectors. Qualitative research methods were used and data were collected through interviews and a literature review. The findings indicated that through the Ministry of Tourism and Sports, the Government is focused on developing the halal industry, including in relation to tourism. The objective of these services is to provide comfort and MICE facilities for Muslim tourists. The government established the Halal Industry Center on the southern border of Pattani province. A halal certification system was also developed in Thailand in collaboration with Chulalongkorn University. The Thai Agricultural Halal Standard (TAS 8400-2007) is the legal umbrella for implementing halal certification, which refers to the international halal standard - Codex. Thailand’s halal food market is growing 20% every year, making it the sixth-ranked country for halal food exports. China, the 57 OIC member countries, the United States, India and Russia are Thailand’s main markets. To promote Thailand’s halal tourism and industry, the government collaborates with ASEAN and Middle East countries and regularly participates in organizing exhibitions and international business forums. The Thai Government’s efforts have had a positive impact on the national income and have contributed to a yearly increase of 10% in the number of Muslim tourists. Keywords: halal industry, halal tourism, Muslim, public diplomacy, Thailand